2021
DOI: 10.1002/adfm.202104487
|View full text |Cite
|
Sign up to set email alerts
|

Use of Nanoformulation to Target Macrophages for Disease Treatment

Abstract: Macrophages are abundant immune cells, which serve as a primary cell population capable of interacting with foreign substances, including engineered nanomaterials (NMs). In addition to the phagocytic activity, macrophages also play a central role in innate immunity and contribute to the initiation of adaptive immunity. Since macrophages are a natural reservoir for NMs, nanoparticles (or nano-enabled strategies) are commonly utilized to target this cell type and fine tune its polarization status in different di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 266 publications
0
11
0
Order By: Relevance
“…[49,83,84] Additionally, the composition of the corona, for example, proteins such as albumin, apolipoprotein E (ApoE), and IgG antibodies, will determine the NMs-cell interactions and cellular uptake mechanisms of liver cells once NMs are distributed in the liver. [85][86][87][88][89][90][91][92][93] Among the different liver cells, most studies are focused on the interactions of NMs with KCs, LSECs, HSCs, and hepatocytes due to their important roles in liver physiology and diseases. The unique liver architecture and location of these liver cells profoundly affect their interaction with NMs and cellular uptake, which will eventually determine the cellular responses (Figure 6).…”
Section: Nms Properties and Cell Type-specific Uptake In The Livermentioning
confidence: 99%
See 1 more Smart Citation
“…[49,83,84] Additionally, the composition of the corona, for example, proteins such as albumin, apolipoprotein E (ApoE), and IgG antibodies, will determine the NMs-cell interactions and cellular uptake mechanisms of liver cells once NMs are distributed in the liver. [85][86][87][88][89][90][91][92][93] Among the different liver cells, most studies are focused on the interactions of NMs with KCs, LSECs, HSCs, and hepatocytes due to their important roles in liver physiology and diseases. The unique liver architecture and location of these liver cells profoundly affect their interaction with NMs and cellular uptake, which will eventually determine the cellular responses (Figure 6).…”
Section: Nms Properties and Cell Type-specific Uptake In The Livermentioning
confidence: 99%
“…The encounter of NMs with the biological environments will form a dynamic corona on NMs surfaces, including proteins, lipids, and certain sugar motifs. [85,86] The structure and composition of the corona are determined by the intrinsic physicochemical properties of NMs, the duration of exposure, and the nature of the physiological environment. [87][88][89] It has shown that the biomolecular corona regulated cellular recognition and penetration of NMs, and further influence their intracellular trafficking.…”
Section: Protein Coronamentioning
confidence: 99%
“…Physicochemical properties of NPs, including their shape, size, surface ligand, and so forth, are crucial factors influencing the cellular uptake and exocytosis processes of the NPs. , Different cells have different properties and functions, , so their responses to different NPs may also be different. For example, cells of different types adopt different endocytic pathways to ingest the same NPs, resulting in different biological effects, for which an example is the higher content of NPs in lysosome destroyed the integrity of the lysosomal membrane. Different types of cells may also have different proliferation rates, which are correlated with different changes in the cellular content of NPs, with the intracellular NPs almost equally distributed into daughter cells after the cell division. ,, Therefore, the cell type must be a pivotal factor affecting the cellular uptake and exocytosis processes of NPs, as recognized in some reported studies. ,, Further more systematic investigations on the exocytosis of NPs in cells aimed at an understanding of the cell-type dependence are in demand …”
Section: Introductionmentioning
confidence: 99%
“…Phagocytosis of NPs can influence TAM polarization because these particles are recognized as foreign bodies. IONPs demonstrated a potent effect on TAM polarization due to iron transporter-related protein expression [ 311 , 312 , 313 ]. Kodali et al [ 314 ] reported 1029 changes in gene expression of lung macrophages using IONPs while silica NPs with only 67 gene.…”
Section: Interaction Of Mnps With Biological Systemmentioning
confidence: 99%